Divergent - Roth, Veronica (National Book Store Inc., 2015)
In a future Chicago, sixteen-year-old Beatrice Prior must choose among five predetermined factions to define her identity for the rest of her life, a decision made more difficult when she discovers that she is an anomoly who does not fit into any one group, and that the society she lives in is not perfect after all.